Simple and Rapid Lateral-Flow Assay for the Detection of Foot-and-Mouth Disease Virus - Oem, Jae Ku (American Society for Microbiology (ASM), 2009)
A simple lateral-flow assay (LFA) based on a monoclonal antibody (MAb 70-17) was developed for the detection of foot-and-mouth disease virus (FMDV) under nonlaboratory conditions. The LFA was evaluated with epithelial suspensions (n = 704) prepared from current and historical field samples which had been submitted to the Pirbright Laboratory (United Kingdom) and from negative samples (n = 100) collected from naïve animals in Korea. Four FMDV serotypes (type O, A, Asia 1, and C) were detected in the LFA, but not the remaining three FMDV serotypes (SAT 1, SAT 2, and SAT 3). The diagnostic sensitivity of the LFA for FMDV types O, A, C, and Asia 1 was similar, at approximately 87.3%, to that of 87.7% obtained with antigen enzyme-linked immunosorbent assay (Ag-ELISA). The diagnostic specificity of the LFA was 98.8%, compared to 100% for the Ag-ELISA. These results demonstrate that the LFA using the FMDV MAb 70-17 to detect FMDV is a supportive method for taking rapid measurements at the site of a suspected foot-and-mouth disease outbreak in Asia before diagnosing the disease in the laboratory, thereby offering the possibility of implementing control procedures more rapidly.